KEKERASAN DALAM KITAB SUCI "Dikehendaki dan Di-amin-i Allah ?" - Tantiono, Paulus T. (LOGOS, 2002)
It is understandable, that many religious people are so offended by theviolence of God as expressed, for example, in the notion of God warriorof war, of God as angry, the notion of hell; that they are troubled inreading or praying the psalms, or the Bible. These notions are quitecontrary to the idea of God in the New Testament as the CompassionateGod, the Loving One, the Ever Forgiving God, The God-Father whoalways wait for His lost-children to return home, etc. How one couldperceive violence throughout the Bible related to God? Does God havetwo-fold faces ? The Good One and the Violent One ?